Barriers to use of modern contraceptives among women in an inner city area of Osogbo metropolis, Osun State, Nigeria - Asekun–Olarinmoye EO; Adebimpe WO; Bamidele JO; Odu OO; Asekun-Olarinmoye IO; Ojofeitimi EO (Dove Medical Press, 2013)
EO Asekun-Olarinmoye,1 WO Adebimpe,1 JO Bamidele,2 OO Odu,2 IO Asekun-Olarinmoye,3 EO Ojofeitimi41Department of Community Medicine, Faculty of Clinical Sciences, Osun State University, Osogbo, Osun State, Nigeria; 2Department of Community Medicine, Faculty of Clinical Sciences, Ekiti State University, Ado-Ekiti, Ekiti State, Nigeria; 3Department of Community Health, School of Public and Allied Health, Babcock University, Ilishan-Remo, Ogun State, Nigeria; 4Department of Community Medicine, Faculty of Clinical Sciences, Ladoke Akintola University of Technology, Osogbo, Osun State, NigeriaObjectives: To determine the knowledge and attitudes on modern contraceptive use of women living in an inner city area of Osogbo.Materials and methods: Three hundred and fifty nine women of childbearing age were studied utilizing a community-based, descriptive, cross-sectional study design. A multistage random sampling technique was used in recruiting respondents to the study. A four-part questionnaire was applied dually, by interviewers and by respondents' self administration, and the data was analyzed using the SPSS software version 17.0.Results: The mean age of respondents was 28.6 ± 6.65 years. The majority (90.3%) of respondents were aware of modern methods of family planning (FP), 76.0% claimed awareness of where to obtain FP services, and 74.9% knew of at least five methods. However, only 30.6% had ever used contraceptives, while only 13.1% were current users. The most frequently used method was the male condom. The commonly perceived barriers accounting for low use of FP methods were fear of perceived side effects (44.0%), ignorance (32.6%), misinformation (25.1%), superstition (22.0%), and culture (20.3%). Some reasons were proffered for respondents' nonuse of modern contraception. Predictors of use of modern contraceptives include the awareness of a place of FP service provision, respondents' approval of the use of contraceptives, higher education status, and being married.Conclusion: Most of the barriers reported appeared preventable and removable and may be responsible for the reported low point prevalence of use of contraceptives. It is recommended that community-based behavioral-change communication programs be instituted, aimed at improving the perceptions of women with respect to bridging knowledge gaps about contraceptive methods and to changing deep-seated negative beliefs related to contraceptive use in Nigeria.Keywords: childbearing age, family planning, fertility desires, perception, knowledge, attitude, benefits